2019
DOI: 10.1074/jbc.ra119.010283
|View full text |Cite
|
Sign up to set email alerts
|

Gating control of the cardiac sodium channel Nav1.5 by its β3-subunit involves distinct roles for a transmembrane glutamic acid and the extracellular domain

Abstract: The auxiliary β3-subunit is an important functional regulator of the cardiac sodium channel Nav1.5, and some β3 mutations predispose individuals to cardiac arrhythmias. The β3-subunit uses its transmembrane α-helix and extracellular domain to bind to Nav1.5. Here, we investigated the role of an unusually located and highly conserved glutamic acid (Glu-176) within the β3 transmembrane region and its potential for functionally synergizing with the β3 extracellular domain (ECD). We substituted Glu-176 with lysine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Additionally, when the helices of each β3 chain are in close proximity, the conserved E176 residue appears to be orientated away from the trimer center and preferentially interacts with the POPC membrane (data not shown). These observations are also supported by recent experimental work examining the role of E176 in β3 subunits, and that also concluded that oligomerization was dependent on the extracellular domain but not E176 (Salvage et al, 2019).…”
Section: Behavior Of the Trimersupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, when the helices of each β3 chain are in close proximity, the conserved E176 residue appears to be orientated away from the trimer center and preferentially interacts with the POPC membrane (data not shown). These observations are also supported by recent experimental work examining the role of E176 in β3 subunits, and that also concluded that oligomerization was dependent on the extracellular domain but not E176 (Salvage et al, 2019).…”
Section: Behavior Of the Trimersupporting
confidence: 80%
“…This glutamate is highly conserved and is found in both β1 and β3 sequences. Given its unusual position, it has been argued that it is likely to have functional significance and indeed has been investigated within β1 (McCormick et al, 1999) and β3 (Namadurai et al, 2014;Salvage et al, 2019). It also seems that for a full-length model based upon the trimeric β3 crystal structure of the ECD to be adopted in the context of a lipid bilayer system, the TMD helices of our model must change their tilt with respect to the membrane normal.…”
Section: The Transmembrane Helix Undergoes a Large Tiltmentioning
confidence: 99%
“…We therefore suggest that unlike β1, the β3-subunit may not play a major role in stabilising the perinexal space by trans -mediated cell-adhesion. On the other hand, when expressed alone in HEK293 cells, the β3-subunits bind homophilically in cis , using their Ig domains [ 19 , 20 , 33 ]. Super-resolution imaging experiments show that when co-expressed with Nav1.5, the β3-subunit affects the relative geometry between Nav1.5 channel α-subunits, possibly by promoting particular orientations of individual Nav1.5 α-subunit dimers within larger clusters [ 20 ].…”
Section: The Nav Channel β-Subunits As Cell-adhesion Moleculesmentioning
confidence: 99%
“…They also shift the voltage ranges over which Nav channel steady-state activation and/or inactivation occur, and in some cases enhance the rates of inactivation and recovery from inactivation [ 18 ]. As an illustrative example, the β3-subunit shifts the V ½ for inactivation of Nav1.5 in a depolarising direction: i.e., the voltage at which half the channels are inactivated is displaced to a more positive value compared to the α-subunit alone ( Figure 3 D) [ 19 , 20 , 21 , 22 ]. For a cardiomyocyte with a resting potential of about -90 mV [ 2 ], this would act to increase the fraction of functional Nav1.5 channels available in the membrane [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation